Red Island House : a novel - Lee, Andrea, 1953- (Scribner, 2021)
"Gorgeously evocative, Red Island House follows two decades in the life of Shay, an African-American professor whose husband Senna, a brash and wealthy Italian businessman, builds her a dream house in Madagascar."--